The Prognostic Value of the Coronary Calcium Score for Detecting Significant Coronary Artery Stenosis Based on CT Coronary Angiography in Patients with Coronary Artery Disease - Mykhailo S. Ishchenko; Olha R. Romaniuk (Ukrainian Journal of Cardiovascular Surgery, 2025)
Coronary artery disease (CAD) is a leading cause of mortality and disability worldwide. CT coronary angiography is a fast and non-invasive method for diagnosing coronary artery pathology. To standardize the assessment of CT coronary angiography results, the CAD-RADS (Coronary Artery Disease – Reporting and Data System) was developed, which is based on determining the degree of coronary artery stenosis. According to recent studies, in addition to CT coronary angiography, an important tool for cardiovascular risk stratification in asymptomatic patients is the assessment of coronary calcium score using the Agatston scale (CAC Score).Aim. To assess the relationship and degree of correlation between the CAC Score and the presence of significant coronary artery stenosis when combining CAC Score and CT coronary angiography.Materials and Methods. The data of 464 patients from the National Institute of Cardiovascular Surgery were analyzed. These patients presented with typical or atypical angina symptoms and had a low or moderate risk of coronary artery disease between September 1, 2024, and January 15, 2025. All patients underwent clinical examination, risk factor assessment, CAC Score evaluation, and CT coronary angiography. Patients with atherosclerosis were divided into two groups: those with non-significant stenosis and those with significant stenosis (≥50% in the left main coronary artery or ≥70% in the major epicardial coronary arteries).Results. The study included 464 patients, predominantly male (55.6%), with a mean age of 59 ± 10.22 years. Atherosclerotic coronary artery disease was detected in 273 patients (58.8%). Based on the CAD-RADS, 24.54% of patients had CAD-RADS 1, 31.14% had CAD-RADS 2, 16.12% had CAD-RADS 3, 20.88% had CAD-RADS 4A, 5.49% had CAD-RADS 4B, and 1.83% had CAD-RADS 5. In the first group (non-significant stenosis), there were 196 patients (71.8%), while the second group (significant stenosis) included 77 patients (28.2%). The median CAC Score in the first group was 24.5 (1–103.25), while in the second group, it was 271.5 (88–666.5), p<0.001. A moderately strong positive correlation was found between the CAC Score and the presence of significant coronary artery stenosis (ρ=0.635, p<0.001). ROC curve analysis shows that the optimal cutoff value of the CAC Score for detecting significant stenosis was 282, with a sensitivity of 48.7%, specificity of 88.8%, and an AUC of 0.819.Conclusions. The study identified a statistically significant correlation between the level of coronary calcification and the presence of significant stenosis. The CAC Score is a reliable prognostic marker for significant coronary artery stenosis in patients with suspected coronary artery disease.